(untitled) (Archives of Mechanics - Test, 2009)
The development of replacement material for human articular cartilage exhibiting similar mechanical properties as the native tissue is a problem of high actuality in biomedicine. In the present work a new condensed collagen material is investigated. The study aims at developing a mechanical model especially adapted to this particular collagen material. For this purpose, a viscoelastic-diffusion (VED) model is proposed, accounting for two different diffusion evolutions assumed. Moreover, the need for a gradient material description is discussed in order to cover fabrication influences leading to a variable Young’s modulus for the material. On this background, a phenomenological law is presented to predict deformation-dependent diffusion behavior and internal reaction forces. Furthermore, the present approach allows a practible identification of diffusion parameters. The theoretical model is implemented into a finite element code and parameters are identified by tension tests. The simulation results are validated experimentally.